Exogenous LEA proteins expression enhances cold tolerance in mammalian cells by reducing oxidative stress - Martina Lo Sterzo; Domenico Iuso; Luca Palazzese; Margherita Moncada; Francesca Boffa; Aurora Scudieri; Luisa Gioia; Marta Czernik; Pasqualino Loi (Scientific Reports)
Abstract Understanding the molecular mechanisms that confer cold resistance in mammalian cells might be relevant for advancing medical applications. This study aimed to exploit the protective function of Late Embryogenesis Abundant (LEA) proteins, known to provide resistance to low temperatures in extremophiles and plants, by their exogenous expression in mammalian cells, and compare their effects with the well characterized antioxidant, vitamin E. Remarkably, the expression of LEA proteins in mammalian cells exerted cold-protective effect similar to Vitamin E. LEA proteins preserved cell viability during cold stress and ensured a normal metabolic activity after warming. Their protective action was due to the mitigation of cold-induced mitochondrial stress and the overproduction of reactive oxygen species (ROS), leading in turn to enhanced cytoskeleton stability and decreased DNA damage. Our studies showed that plant-derived LEA proteins exhibit remarkable cold protection effects in mammalian cells through their potent antioxidant properties, which was found comparable to Vitamin E.